A Theoretical Model for the Cross-Flow Induced Fluid-Elastic Instability in Heat Exchanger Tube Bundles - Lever, Howard James (My University, 1983)
A simple theoretical model has been developed from first princples for the cross-flow induced fluid-elastic instability in heat exchanger tube bundles. A series of experiments were conducted to verify the basic assumption that only a single tube need be modelled in a flow channel which preserves the basic geometry of the array. The mechanism of dynamic instability is found to be one of flow redistribution due to transverse tube motion and a phase lag resulting from fluid inertia. Static instabilities in both streamwise and transverse directions are also predicted, but at higher reduced flow velocities than the transverse dynamic instability. Quite good agreement is found with available experimental data, particularly for parallel triangular and square arrays, without the need for empirical fluid force coefficients. The model includes the effects of tube array pattern and pitch.
Keywords: Mechanical Engineering; Mechanical Engineering